Rational Design of Carboxyl Groups Perpendicularly Attached to a Graphene Sheet: A Platform for Enhanced Biosensing Applications. Issue 1 (5th December 2013) - Bonanni, Alessandra; Chua, Chun Kiang; Pumera, Martin
Abstract Graphene oxide (GO)‐based materials offer great potential for biofunctionalization with applications ranging from biosensing to drug delivery. Such biofunctionalization utilizes specific functional groups, typically a carboxyl moiety, as anchoring points for biomolecule. However, due to the fact that the exact chemical structure of GO is still largely unknown and poorly defined (it was postulated to consist of various oxygen‐containing groups, such as epoxy, hydroxyl, carboxyl, carbonyl, and peroxy in varying ratios), it is challenging to fabricate highly biofunctionalized GO surfaces. The predominant anchoring sites (i.e., carboxyl groups) are mainly present as terminal groups on the edges of GO sheets and thus account for only a fraction of the oxygen‐containing groups on GO. Herein, we suggest a direct solution to the long‐standing problem of limited abundance of carboxyl groups on GO; GO was first reduced to graphene and consequently modified with only carboxyl groups grafted perpendicularly to its surface by a rational synthesis using free‐radical addition of isobutyronitrile with subsequent hydrolysis. Such grafted graphene oxide can contain a high amount of carboxyl groups for consequent biofunctionalization, at which the extent of grafting is limited only by the number of carbon atoms in the graphene plane; in contrast, the abundance of carboxyl groups on "classical" GO is limited by the amount of terminal carbon atoms. Such a graphene platform embedded with perpendicularly grafted carboxyl groups was characterized in detail by X‐ray photoelectron spectroscopy, cyclic voltammetry, and electrochemical impedance spectroscopy, and its application was exemplified with single‐nucleotide polymorphism detection. It was found that the removal of oxygen functionalities after the chemical reduction enhanced the electron‐transfer rate of the graphene. More importantly, the introduction of carboxyl groups promoted a more efficient immobilization of DNA probes on the electrode surface and improved the performance of graphene as a biosensor in comparison to GO. The proposed material can be used as a universal platform for biomolecule immobilization to facilitate rapid and sensitive detection of DNA or proteins for point‐of‐care investigations. Such reactive carboxyl groups grafted perpendicularly on GO holds promise for a highly efficient tailored biofunctionalization for applications in biosensing or drug delivery.